Short-term benefit of smoking cessation along with glycopirronium on lung function and respiratory symptoms in mild COPD patients: a retrospective study. (6th August 2018) - Pezzuto, Aldo; Stellato, Marco; Catania, Giovanna; Mazzara, Calogero; Tonini, Sara; Caricato, Marco; Crucitti, Pierfilippo; Tonini, Giuseppe
Abstract: Introduction. Tobacco smoke is the leading cause of chronic obstructive pulmonary disease (COPD). Smoking cessation can change the natural history of COPD, as we know from the GOLD guidelines. Little is known about the short-term clinical and functional effects of smoking cessation treatment combined with anti-muscarinic bronchodilators. Objective. To determine whether quitting smoking, obtained by smoking cessation treatment combined with the use of a new long-acting muscarinic antagonist bronchodilator (LAMA), can improve lung function tests and respiratory symptoms more than the use of LAMA alone. Methods. We evaluated, in a retrospective analysis, the functional and clinical data, collected in one year, of 120 patients who were current smokers affected by mild COPD and who quit smoking using smoking cessation treatment combined with glycopirronium. We compared them with a group of 80 patients with mild COPD undergoing the same treatment but who did not quit smoking. All patients underwent functional and clinical tests at baseline and at a third-month check. Measurements and main results. The two groups were homogeneous in terms of demographic data without significant differences. All patients used varenicline for smoking cessation. They all performed the following tests: a spirometry with detection of resistances, the 6 min walking test, haemogasanalysis, the exhaled CO test, the COPD assessment test (CAT) and finally the modified Medical Research Council test (mMRC). A significant improvement in the functional tests at the third-month check was found in both groups—quitters and non-quitters. However, a notable increase in the examined parameters was registered in the group of patients who quit smoking, in particular, we observed a significant increase at the third-month check of the parameter forced expiratory volume in 1 s (FEV1) of more than 200 ml with p  < 0.001. A comparison between quitters and non-quitters revealed a major benefit derived from smoking cessation in terms of functional changes and symptom relief. In particular, not only FEV1 but also forced expiratory flow at 25%–75% of vital capacity (FEF 25–75) ( p  < 0.01) and CAT ( p  < 0.001) were found to be significantly improved in patients who quit than in patients who did not at the check time point. Conclusions. Smoking cessation treatment obtained by varenicline was confirmed as a crucial therapeutic option, especially when combined with bronchodilator in mild COPD. Patients who quit smoking could already benefit from both treatments in the short term, improving lung function and respiratory symptoms and therefore improving their quality of life.